DOI: 10.1007/978-3-540-74997-4_26
|View full text |Cite
|
Sign up to set email alerts
|

Attentive Presentation Agents

Abstract: Abstract. The paper describes an infotainment application where lifelike characters present two MP3 players in a virtual showroom. The key feature of the system is that the presenter agents analyze the user's gaze-behavior in real-time and may thus adapt the presentation flow accordingly. In particular, a user's (non-)interest in interface objects and also preference in decision situations is estimated automatically by just using eye gaze as input modality. A formal study was conducted that compared two versio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 17 publications
0
24
0
Order By: Relevance
“…In the earlier experiment, the interactive agent was perceived as more responsive than the non-interactive agent. The subjects felt, however, also more disturbed by the perceptive agent [Eichner et al, 2007]. Obviously, the users enjoyed the interactive version more and found it more engaging without perceiving it, however, as more interactive.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In the earlier experiment, the interactive agent was perceived as more responsive than the non-interactive agent. The subjects felt, however, also more disturbed by the perceptive agent [Eichner et al, 2007]. Obviously, the users enjoyed the interactive version more and found it more engaging without perceiving it, however, as more interactive.…”
Section: Discussionmentioning
confidence: 94%
“…Dependent on the duration and focus of the user's gaze further details of the scene are described via a text-to-speech system. Another exception includes the work by [Eichner et al, 2007] who made use of an eye tracker. In an experiment, they showed that agents that adapted the content of their presentation to a user's eye gaze were perceived as more natural and responsive than agents that did not have that capability.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The focus of that work is the regulation of conversational flow in a multiagent environment. Unlike Vertegaal and colleagues, Eichner and colleagues [5] who made use of an eye tracker to detect interest and attentiveness in a virtual presentation In an experiment, they showed that agents that adapted the content of their presentation to a user's eye gaze were perceived as more natural and responsive than agents that did not have that capability.…”
Section: Related Workmentioning
confidence: 95%
“…For instance, the gaze of the user follows the agent's deictic gesture to some visual reference object, and subsequently returns to the agent's face, apparently awaiting further information from the interface agent. Based on these findings, a new generation of virtual infotainment agents, the so-called ''visual attentive presentation agents'', have been implemented [27]. 1 These agents monitor the user's gaze behaviour during their performance, and adapt their presentation to the user's visual interest (or lack of it).…”
Section: Attentive Interfaces For Users With Disabilitiesmentioning
confidence: 99%